2019
DOI: 10.1111/apa.14835
|View full text |Cite
|
Sign up to set email alerts
|

Population‐based register study of children born in Sweden from 1997 to 2014 showed an increase in rickets during infancy

Abstract: Aim: This population-based study assessed the incidence of rickets in infants up to age of one born in Sweden from 1997 to 2014. We also examined maternal and perinatal factors and co-morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(56 reference statements)
2
4
0
1
Order By: Relevance
“…Our data are in agreement with those of a meta‐analysis performed by Revuelta et al, who reported that most studies emanating from Europe and North America, published after the year 2000, found higher prevalence of vitamin D deficiency among children with cancer than those published in the 1980s and the 1990s 10 . In line with our results, studies have indicated an increased prevalence of vitamin D deficiency and rickets in the general paediatric population in Northern Europe 20,21 and recognised this as a rising health issue. Possible causes for this trend could be (a) changes in lifestyle, such as less time spent playing outdoors and use of more sun protection due to an increased awareness of the risk of skin cancer, 22 (b) an increasing proportion of children with obesity, 23 (c) changes in the ethnic composition of the Swedish population with an increase in the number of children with dark skin, and (d) changes in Swedish guidelines for vitamin D supplementation 24…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in agreement with those of a meta‐analysis performed by Revuelta et al, who reported that most studies emanating from Europe and North America, published after the year 2000, found higher prevalence of vitamin D deficiency among children with cancer than those published in the 1980s and the 1990s 10 . In line with our results, studies have indicated an increased prevalence of vitamin D deficiency and rickets in the general paediatric population in Northern Europe 20,21 and recognised this as a rising health issue. Possible causes for this trend could be (a) changes in lifestyle, such as less time spent playing outdoors and use of more sun protection due to an increased awareness of the risk of skin cancer, 22 (b) an increasing proportion of children with obesity, 23 (c) changes in the ethnic composition of the Swedish population with an increase in the number of children with dark skin, and (d) changes in Swedish guidelines for vitamin D supplementation 24…”
Section: Discussionsupporting
confidence: 93%
“…Case series have reported long bone shaft fractures associated with metabolic bone disease of infancy [21]. We found only few shaft fractures with a diagnosis of rickets or vitamin D de ciency, as previously reported for fractures of any type [22].…”
Section: Discussionsupporting
confidence: 73%
“…Infants that were entered in the National Patient Register (NPR), but without birth-related or other fractures during the neonatal period served as controls as previously described. 18…”
Section: Controlsmentioning
confidence: 99%